Методи та засоби персоніфікації інформаційного наповнення у глобальній системі World Wide Web - Березко, Олександр Леонідович (Національний університет "Львівська політехніка", 2011)
У дисертації розроблено методи та засоби персоніфікації інформаційного наповнення у глобальній системі World Wide Web. Побудовано спеціальні персоніфікаційні моделі структури та історії інформаційного наповнення у WWW; запропоновано систему формальних показників веб-сайтів, веб-сторінок та дописів. Розроблено метод активної реферальної персоніфікації із використанням суспільних акцій у WWW, що дає змогу ефективно створювати персоніфікаційні зв’язки; метод пасивної віддаленої персоніфікації із застосуванням спеціалізованого веб-каталогу та метод змішаної віддаленої персоніфікації з використанням wiki-спільнот, за допомогою яких можна описувати веб-особистості та їхні елементи. Розроблено комплекс програмних засобів персоніфікації інформаційного наповнення, який дає змогу залучати глобальну веб-спільноту до процесу персоніфікації та підвищує її ефективність. В диссертации разработано методы и средства персонификации информационного наполнения в глобальной системе World Wide Web. Построены специальные персонификационные модели структуры и истории информационного наполнения в WWW; создана система формальных показателей сайтов, веб-страниц и сообщений. Разработан метод активной реферальной персонификации с использованием общественных акций в WWW, что позволяет эффективно создавать персонификационные связи, а также метод пассивной удаленной персонификации с введением специализированного веб-каталога. Предложен метод смешанной удаленной персонификации с использованием wiki- сообществ, с помощью которых можно описывать веб-личности и их элементы. Разработан комплекс программных средств персонификации информационного наполнения, позволяющий привлекать глобальное веб-сообщество к процессу персонификации и повышать ее эффективность.The thesis deals with solving an important scientific task of developing methods and means of WWW content personification. In the thesis special personification models of structure and history of web content as well as a system of formal indexes of websites, web pages and posts were developed. Means of active referral personification by means of web-oriented public actions, passive remote personification through the use of specialized web directory and mixed remote personification by means of wikis were suggested. Software which allows to involve global web community in the process of web content personification and improves personification efficiency was developed. In the first chapter current tendencies of WWW development, particularly the concept of Web 2.0, were analyzed. Main types of web communities as well as peculiarities of their users’ creative activity and user-generated content in general were analyzed. Besides, the analysis of web content personification in comparison with other digital online identity and WWW user reputation means was carried out. This part of the research formed the basis for web content modeling and further work. In the second chapter the general description of user-generated content from the point of view of personification was made. Formal model of web content which includes model of web content structure based on the analysis of modern web communities’ content hierarchy and model of web content history based on the analysis of WWW users’ networking was developed. In addition, a special set of formal indexes of websites, web pages and posts was presented. These indexes enabled improving of the web content classification, which is used for describing parts of web content. Further in this chapter the concept of “web personality” was defined and formalized and method of website’s content personification level assessment was suggested. The research results presented in this chapter were used as a theoretical background for further development of means and tools of web content personification. In the third chapter methods and algorithms of web content personification were introduced. At the beginning of the chapter all the major personification methods are analyzed and requirements for such methods are formulated. Further, the methods and algorithms of active referral personification with the use of web-oriented public actions including the methods of multiple simultaneous public actions organizing were presented. Besides, a method of passive remote personification with the use of specialized directory of web personalities was suggested as well as a method of mixed remote personification with the use of wiki-based communities. A set of special wiki templates for such communities was presented. In the fourth chapter the software, algorithmic and informational means and tools of web content personification are presented. The main components of the software complex, which are the directory of web personalities, hosting of web-oriented public actions and specialized wiki-communities were developed. Also their functions and technical aspects of realization were described. Further, the author analyzed the personification level of a set of web communities in which the research results and the software complex in particular were applied. Experimental studies proved the correctness of the formulation of the problem, the accuracy of the suggested formal models and efficiency of the developed methods and means of personification.
Методы и средства персонификации информационного наполнения в глобальной системе World Wide Web
Means and tools of World Wide Web content personification
Keywords: Internet; World Wide Web; content; personification; virtual community; Интернет; World Wide Web; информационное наполнение; персонификация; веб-сообщество; Інтернет; World Wide Web; інформаційне наповнення; персоніфікація; веб-спільнота